Al-Ma’had al-Turāthī wa Tajdīd al-Niẓām al-Ta’līmī bi Indūnīsiyā - Fachruddin, Fuad; Abbas, Sirojuddin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
This article explores some aspects of pesantren education with respect to the plan to consolidate the administration of both Islamic and secular education system. This is an important matter since there are certain basic weaknesses in the national educational system that call for attention, including problems of students' empowerment and the content of education. Since pesantren has a relatively good record in training and education, it can contribute its experience in the development of national education as whole. Previous studies show that the system of pesantren education has two strengths. First, the presence of a strong interest in learning among the santi (students of pesantren) or, in educational terms, a high level of mastery learning. The second aspect in which pesantren is strong is in the participation of community. The establishment of pesantrens all over Indonesia basically reflected the demand as well as the need of communities themselves, and because of that the participation of communities in running individual institutions is quite high.DOI: 10.15408/sdi.v7i1.719